Assisted Interactive Learning Media Innovation Application Microsoft Sway - Sumanti, Sumanti; Marliza, Marliza; Khairani, Cut (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
This research aims to obtain validation of the development of interactive learning media assisted by applications Microsoft Sway to improve students' critical thinking skills. The type of research is Research and Development (R&D), using the Plomp model (2013). This research involves expert validators are material experts, language experts, media experts, and IT experts. The development stages include preliminary research(preliminary research), level prototype/product development stage (prototyping phase), evaluation level (assessment phase), and systematic reflection and documentation. The data collection method uses sheets self-evaluation, validation sheet prototype, observation sheets, interviews, and sheets Focus Group Discussion (FGD). The collected data was analyzed using SPSS. The validity and usability of product designs are measured through formative evaluation, including self-evaluation. Summative evaluation is carried out at the assessment stage to determine product validity. The research product consists of interactive learning media assisted by applications Microsoft Sway and product use manuals. The research results show that the media Microsoft Sway The results generated are declared valid, where for the media value the Correlation Coefficient (ICC). The results obtained were very high = 0.968 from the average inter-agreement results rater, while for one rater the consistency is 0.400. For the guidebook, the value ICC obtained is also very high = 0.958 from the analysis of the average agreement between raters, while for one rater the consistency is 0.360. Overall it can be said to be an interactive learning media assisted by applications Microsoft Sway and a valid and usable Guidebook.